Numerical investigation of flow boiling characteristics in cobweb-shaped microchannel heat sink - Juncheng Qiu (Elsevier, 2021)
In recent years, researchers have conducted extensive studies on the improvement of heat transfer performance of microchannels, however, exploiting biomimetic microchannels to enhance the flow boiling heat transfer performance is still relatively rare. In this study, inspired by the cobweb structures in nature, cobweb-shaped microchannels with horizontal inlet and outlet (CMHS-H) and cobweb-shaped microchannels with inclined inlet and outlet (CMHS-I) are proposed. Flow boiling simulations are carried out with the inlet temperature of 300 K at the bottom heat flux of 75–125 W/cm2 under different mass fluxes by utilizing volume of fluid (VOF) model. The flow boiling characteristics of the CMHS-I and CMHS-H are studied and compared with those of the rectangular microchannel heat sink (RMHS). The results demonstrate that both the CMHS-H and CMHS-I can enhance the heat transfer coefficient and reduce the wall temperature due to the flow disturbance and increased heat transfer area; whereas the CMHS-H is effective to reduce the pressure drop and suppress the flow instability at high mass flux. At high heat flux, the CMHS-H shows the best heat transfer performance and the most stable flow boiling behavior. This study provides a promising approach of using biomimetic microchannels to dissipate high heat flux associated with advanced electronics.